The Effectiveness of Traditional Traps Fishing Gear (Bubu) at Nusantara Fishing Port of Tanjungpandan (NFPT), Belitung Regency - Silvi Afriyansih Vivi; Sudirman Adibrata; M. Rizza Muftiadi; Mohammad Oka Arizona (Yayasan Serumpun Karang Konservasi, 2023)
Bubu is a non-selective fishing gear in which the types of fish caught varied, especially demersal. Among several fishing gears, bubu has high economic value, so the demand for fisheries resources caught by bubu has increased. This research aims to identify the construction of a particular fishing gear (bubu) and analyze its caught result effectiveness. The research was conducted from March- April 2022 in Nusantara Fishery Port (PPN) Tanjungpandan, Belitung Regency. Methods used in this research were descriptive analyses, which collected the data directly through interviews with the key person fishermen who used bubu. The number of critical persons is determined using the census method, resulting in 46 key persons being interviewed. The methods used to identify the effectiveness of caught results were seen from the main species caught, production per trip, fishing ground, and fishing gear construction. Results showed that bubu has constructions consisting of a body frame made of wood and rattan, a mouth frame made of wires, with 100-155 cm length, 60-165 cm wide, 20-85 cm height, and the outer mouth diameter is 30-50 cm, mouth wide is 10-25 cm while the inner mouth diameter is 20 cm with 3 cm mesh size. The effectiveness of bubu as the fishing gear was 80%, and it showed that bubu was practical to use.